2020
DOI: 10.3390/app10051891
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble of Locally Reliable Cluster Solutions

Abstract: Clustering ensemble indicates to an approach in which a number of (usually weak) base clusterings are performed and their consensus clustering is used as the final clustering. Knowing democratic decisions are better than dictatorial decisions, it seems clear and simple that ensemble (here, clustering ensemble) decisions are better than simple model (here, clustering) decisions. But it is not guaranteed that every ensemble is better than a simple model. An ensemble is considered to be a better ensemble if their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 54 publications
(62 reference statements)
0
20
0
Order By: Relevance
“…But these methods use hard clustering as base clustering algorithm. Recently soft clustering algorithms [27] have been popular and it has been shown that these methods are superior to traditional hard clustering algorithms [28] , [29] , [30] . We can use soft clustering and fuzzy clustering interchangeably.…”
Section: Methodsmentioning
confidence: 99%
“…But these methods use hard clustering as base clustering algorithm. Recently soft clustering algorithms [27] have been popular and it has been shown that these methods are superior to traditional hard clustering algorithms [28] , [29] , [30] . We can use soft clustering and fuzzy clustering interchangeably.…”
Section: Methodsmentioning
confidence: 99%
“…Clustering of sequences is the process of bringing similar motifs together as a cluster. Different clustering approaches have been previously used to group biological and nonbiological data [ 17 , 18 , 19 , 20 ]. Clustering of sequences gives the user the ability to observe each group separately, identify similar patterns among samples in the same group, identify differences between different clusters, and find the most important motifs in each group.…”
Section: Methodsmentioning
confidence: 99%
“…The value of the movement probability function is computed in every step from the relation exp(-ΔF/T). The difference between this equation and the object function is the value for the current and the new solution [26,29,30]. Theoretically, overcoming local optimization, the SA technique is able to find the absolute optimized solution.…”
Section: The Techniquementioning
confidence: 99%